Why Vote with the Chief? Political Connections and Public Goods Provision in Zambia. Issue 4 (12th April 2013) - Baldwin, Kate
<x xml:space="preserve">Abstract</x> Why are voters influenced by the views of local patrons when casting their ballots? The existing literature suggests that coercion and personal obligations underpin this form of clientelism, causing voters to support candidates for reasons tangential to political performance. However, voters who support candidates preferred by local patrons may be making sophisticated political inferences. In many developing countries, elected politicians need to work with local patrons to deliver resources to voters, giving voters good reason to consider their patron's opinions of candidates. This argument is tested using data from an original survey of traditional chiefs and an experiment involving voters in Zambia. Chiefs and politicians with stronger relationships collaborate more effectively to provide local public goods. Furthermore, voters are particularly likely to vote with their chief if they perceive the importance of chiefs and politicians working jointly for local development.